THE USE OF FEATURE FILMS IN THE TRAINING PROCESS OF FUTURE JOURNALISTS - Oleg Semeniuk (Інтегровані комунікації)
The potential of cinema for use in the educational process remains relatively high. Researchers emphasize the characteristics of feature films that allow them to be used as an effective learning tool: they are a synthetic audiovisual medium that adds dynamism to the learning process; they can create the effect of an active participant in communication, stimulating cognitive activity; they allow the introduction of sociocultural information into the process, which contributes to the expansion of additional knowledge; due to their high artistic and aesthetic value, they have an educational impact. All this highlights the relevance of research exploring the methods of using films in education, particularly in higher education institutions.